Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/acs.macromol.5b00091
|View full text |Cite
|
Sign up to set email alerts
|

Robust Amidation Transformation of Plant Oils into Fatty Derivatives for Sustainable Monomers and Polymers

Abstract: Sustainable fuels, chemicals, and materials from renewable resources have recently gained tremendous momentum in a global scale, although there are numerous nontrivial hurdles for making them more competitive with petroleum counterparts. We demonstrate a robust strategy for the transformation of plant oils into polymerizable monomers and thermoplastic polymer materials. Specifically, triglycerides were converted into N-hydroxyalkyl fatty amides with the aid of amino alcohols via a mild base-catalyzed amidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 68 publications
2
58
0
1
Order By: Relevance
“…Tang et al [ 16 ] reported on the synthesis of N -hydroxyalkylamides and methacrylate hydrophobic monomers through the interaction of plant oil triglycerides with amino alcohols ( Figure 1 ). They developed a new interesting approach that involves the use of a two-step process.…”
Section: Features Of Synthesis Of Vinyl Monomers From Plant Oilsmentioning
confidence: 99%
“…Tang et al [ 16 ] reported on the synthesis of N -hydroxyalkylamides and methacrylate hydrophobic monomers through the interaction of plant oil triglycerides with amino alcohols ( Figure 1 ). They developed a new interesting approach that involves the use of a two-step process.…”
Section: Features Of Synthesis Of Vinyl Monomers From Plant Oilsmentioning
confidence: 99%
“…Diels−Alder reactions can also be exploited as a tool for post‐polymerization of bio‐derived polymers. Tang and co‐workers developed fatty‐acid‐derived poly(meth)acrylates by a transesterification of vegetable oil with ethanol amine . The unsaturated fatty acid pendants were modified via thiol‐ene click chemistry to introduce furan moieties, which can be used as dienes in Diels−Alder reactions (Scheme ) .…”
Section: Post‐polymerization Modification Via Ccmentioning
confidence: 99%
“…Indeed, recently, Maiti et al reported a new method of functionalization involving Steglich esterification of various FA (caprylic, capric, lauric, myristic, palmitic, stearic, and oleic acids [OLA]) to provide partially biobased methacrylate monomers in a one‐step method (Maiti et al, ; Maiti and De, ). Another synthetic route based on a two‐step method through amidation followed by (meth)acrylation has been recently reported by Yuan et al to provide monomers for radical polymerization (Yuan et al, ). Similarly, to find other bioalternatives, our previous work focused on the synthesis of an OLA‐based monomer, 2‐(methacryloyloxy)ethyl oleate (MAEO), which was successfully involved in free radical polymerization (FRP) and evaluated as VII (Lomège et al, ).…”
Section: Introductionmentioning
confidence: 99%